Análise fisiológica, bioquímica e proteômica de respostas ao estresse hidrico em genótipos de feijão-caupi [Vigna unguiculata (L.) Walp. ] - Lima, Eveline Nogueira (2017)
A physiological, biochemistry and proteomic studies were conducted on cowpea [Vigna unguiculata (L.) Walp.)], aiming to identify mechanisms involved in drought tolerance or susceptibility by using three different approaches. The importance of these studies is based on the fact that cowpea is a nutritional and economically crop cultivated mainly in the water deficient semiarid region of the Northeast of Brazil. Three experiments were conducted, two in a greenhouse and one in the laboratory. The objective of the first trial was to identify genotypes that were tolerant or susceptible to water deficit by using two approaches: (a) water deficit simulated by the use of PEG6000 (Polyethylene glycol) and (b) by Screening Box. The results of these trials revealed that the two methodologies were efficient to allowed the selection of cowpea “Pingo de Ouro 1,2” genotype as being tolerant to water deficit, while the “Santo Inácio Vermelho” genotype was found to be susceptible. The second trail aimed to look for understanding the mechanism underlying plants tolerant to drought by means of physiological and biochemistry characterization of drought tolerance in the contrasting genotypes susceptible. A completely randomized design (CRD) was used in a 4x2 factorial arrangement. The physiological responses, as measured by gas exchange, chlorophyll at the flowering stage, photosynthetic pigments, membrane damage by lipid peroxidation (DPL), and determination of organic solutes (Proline, Soluble Carbohydrates and N-amino acids) were characterized. Some mechanisms were effectives in identifying the “Pingo de Ouro 1,2” genotype tolerance to stomata conductance to water (gs). This observation showed the efficiency in the stomata control, the ratio of liquid assimilation rate and stomata conductance to stream (A/gs), water use efficiency (A/E), providing greater efficiency of water use in the tolerant genotype. The carboxylation efficiency and the total chlorophyll that had their values recovered when the genotype was irrigated again after the four days of severe water deficit, which indicated that the mentioned genotype can tolerant a longer period of drought. The goals of the third trial were to identify the differentially expressed proteins and proteins responses to the water deficits in the experimental genotypes of the trial number 2. Proteins were extracted from leaves, while the control treatments irrigated show moderate water deficit (-1,0 MPa) and severe deficit (-1,5 MPa) of each tolerant and sensitive water deficit genotype were evaluated by 2D-SDS PAGE, using mass spectrometry for identification of proteins. Within all the comparisons, 108 differentially expressed proteins were identified that were involved in several cellular pathways that affected the two genotypes. Proteins were identified both in the tolerant “Pingo de Ouro 1,2” genotype as well as in the susceptible to water deficit “Santo Inácio Vermelho” genotype. The conclusion is that these genotypes could be used as markers. The proteins that were most expressed among the mentioned genotypes, was the subunit of major partial ribulose-1,5 bisphosphate carboxylase/oxigenase, (chloroplast), and a difference was found between these proteins. Considering the described situation, it can be assumed that the tolerance has more efficient mechanisms of dry escape than the sensitive one. The results indicated information for understanding the molecular bases of tolerance and sensible cowpea genotypes under water deficit.